Review of Omega-3 Fatty Acids for the Treatment of Attention Deficit/Hyperactivity Disorder - Jamie N. Brown; Nicole Panosh (SAGE Publishing, 2009)
Objective To review the efficacy of omega-3 fatty acids in the treatment of attention deficit/hyperactivity disorder (ADHD). Data Souces Literature was accessed via MEDLINE (1950-February 2009) and International Pharmaceutical Abstracts (1960-2009) using the medical subject heading terms omega-3 fatty acids and attention deficit disorder with hyperactivity. Additional references were found by searching bibliographic references of resulting citations. Study Selection and Data Extraction All English-language, placebo controlled publications identified were analyzed for significance. Studies relevant to the objective were used, including eight studies evaluating the use of omega-3 fatty acid in the treatment of children with symptoms of ADHD. Data Synthesis Omega-3 fatty acid supplementation has been found to have variable efficacy in the treatment of patients with ADHD. Of the eight studies evaluated, three demonstrated no significant improvements in any evaluation criteria, with five studies reporting positive effects in at least one outcome measure. All positive efficacy studies included concomitant supplementation with omega-6 fatty acids. No clinically significant adverse effects were identified in the reviewed studies. Conclusions Based on the available data, current fatty acid supplementation techniques do not appear to be a consistant method of controlling ADHD symptoms. Without better evidence to determine the true value of fatty acids in the treatment of ADHD, omega-3 fatty acid use should be isolated to adjuvant supplementation or used in patients unable or unwilling to take stimulant medications. If recommended, there does not appear to be clinically significant adverse events associated with omega-3 fatty acid supplementation and this would be a safe treatment modality.